2008
DOI: 10.1007/s11664-008-0540-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress State on Growth of Interfacial Intermetallic Compounds Between Sn-Ag-Cu Solder and Cu Substrates Coated with Electroless Ni Immersion Au

Abstract: Excessive intermetallic compound (IMC) growth in solder joints will significantly decrease the reliability of the joints. IMC growth is known to be influenced by numerous factors during the component fabrication process and in service. It is reported that, other than temperature and holding time, stress can also influence the IMC growth behavior. However, no existing method can be used to study the effect of stress state on IMC growth in a controlled manner. This paper presents a novel method to study the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(3). This stress value seems small compared with others' work on the influence of external in-plane stress on Cu-Sn IMC [8]. But the yield strength of pure tin at 150 °C is 7.6 MPa [11].…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…(3). This stress value seems small compared with others' work on the influence of external in-plane stress on Cu-Sn IMC [8]. But the yield strength of pure tin at 150 °C is 7.6 MPa [11].…”
Section: Methodsmentioning
confidence: 66%
“…Among the literature, Vianco et al [7] first reported the influence of external stress on the IMC growth during aging. Ngoh et al [8] designed a C-ring to induce in-plane stress on the solder/substrate interface, and an increase in IMC growth rate was found when compressive stress was applied. Similar results were also revealed by Hu et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…13(a) and (b). It has been reported that compressive stress leads to outdiffusion of copper and surface metallization into solder, and facilitates IMC growth [22]. Hence, it can be estimated that the fatigue life of the solder interconnection will deteriorate as the interposer size increases, due to increase in the warpage and accelerated growth of IMC layer.…”
Section: B Effect Of Interposer Size On Interconnection Reliabilitymentioning
confidence: 99%
“…Vianco et al 6 reported that residual stresses enhance the growth of an intermetallic compound layer at the interface between Au–Pt–Pd foil and Sn–Pb eutectic alloy. Ngoh et al 7 and Liao et al 8 also reported enhancement of the interfacial reaction due to stress. These reports show that the stress in the iron layer affects the interfacial reaction between the solid iron layer and the solid solder alloy.…”
Section: Introductionmentioning
confidence: 95%